Odgovornost projektanta za napake gradbe - Ravbar, Ivan (Podjetje in delo, 2017)
The article explains the legal nature of designer's liability for defects in construction and claims brought by clients against designers.
Keywords: buildings defects; designer's liability; napaka gradbe; napaka projekta; odgovornost projektanta; pogodba o izdelavi projekta; project contract; project defects